The Relationship of Economic Freedom and Governance Quality on the Unemployment Rate in Selected Asian countries - Man, Lim Bao; Rahman, Nuzlinda Abdul; Arsad, Zainudin (CENTRAL ASIA AND THE CAUCASUS, 2021)
Unemployment rate (UE) is always a concern in labour market view globally. This study investigates the assumption that the greater the degree of economic freedom and good governance quality, it will reduce a country’s unemployment rate, ceteris paribus, for several Asian nations from the year 2002 to 2018. Static panel data analysis is applied in this study. Fixed effect model (FEM) is the most suitable modelto estimate the unemployment rate in selected Asian countries. From FEM, the variables Investment Freedom and Voice and Accountability show positive relationship with unemployment rate since these variables have positive coefficients. On the contrary, the Tax Burden, Government Spending, Labour Freedom and Political Stability No Violence show negative relationship with unemployment rate. In conclusion, it is important to understand the unemployment rate in selected Asian countries because it will shape the comparative advantage and describe the situation of Asian labour market. This study provides an overview of unemployment rate using an appropriate statistical modelling known as panel data approach.